Covid-19 Kills More Men Than Women: An Overview of Possible Reasons - Capuano, Annalisa; Rossi, Francesco; Paolisso, Giuseppe (Frontiers in Cardiovascular Medicine, 2020)
The high mortality observed in Covid-19 patients may be related to unrecognized pulmonary embolism, pulmonary thrombosis but also to other underlying cardiovascular diseases. Recent data have highlighted that the mortality rate of Covid-19 seems to be higher in male patients compared to females. In this paper we analyzed possible factors that may underline this gender difference, in terms of activity of the immune system and its modulation by sex hormones, coagulation pattern and preexisting cardiovascular diseases and effects deriving from smoking and drinking habits. Future studies are needed to evaluate the effects of sex differences on the prevalence of infections, including Covid-19, their outcome and responses to antiviral treatments.